Flow-field effects on gas removal and electrolyte distribution in water electrolyzers: a CFD study - Inamdar, Madhura; Dastane, Gaurav (Industrial & Engineering Chemistry Research, 2026)
This study aims to provide a simplified 3D modeling approach for two-phase flow in electrolyzers. Low-temperature electrolyzers operating at high current density exhibit inefficient gas bubble removal, leading to mass-transfer resistance for the electrolyte. To outline an effective gas-removal mechanism, studying two-phase flow dynamics in the porous transport layer (PTL) and flow channels through CFD modeling is essential. Subsequently, a few common flow field designs (serpentine, straight parallel, and inclined parallel) are compared for the two-phase flow dynamics. A modified flow field design is proposed, which allows electrolyte redistribution in the x, y, and z directions and better electrolyte penetration in the PTL. The developed model provides insight into flow and phase interactions along the flow path, aiding in the efficient design of flow fields. The study concludes that the proposed flow field design offers advantages over the conventional design, including greater electrolyte interaction with the PTL and improved gas removal.